Nano-Selenium Alleviates Cadmium-Induced Acute Hepatic Toxicity by Decreasing Oxidative Stress and Activating the Nrf2 Pathway in Male Kunming Mice - Du, Hong; Zheng, Yilei; Zhang, Wei; Tang, Huaqiao; Jing, Bo; Li, Haohuan; Xu, Funeng; Lin, Juchun; Fu, Hualin; Chang, Lijen; Shu, Gang (Frontiers in Veterinary Science, 2022)
Cadmium (Cd) is known as a highly toxic heavy metal pollutant and has been reported to cause hepatotoxicity in animals. Nano-selenium(NSe) is an antioxidant that has been shown to alleviate oxidative stress. The purpose of this study was to explore the mechanism by which NSe inhibits Cd-induced hepatic toxicity and oxidative stress. Sixty eight-week-old male Kunming mice were randomly divided into four groups (15 mice per group). The control group and cadmium groups received distilled water, whereas the sodium-selenite group received 0.2 mg/kg Se and the nano-selenium group received 0.2 mg/kg NSe intragastrically for two weeks. Except the control group, all the other groups were treated with Cd (126 mg/kg b.w) on the last day. The results showed that NSe alleviated Cd-induced hepatic pathological changes. Furthermore, NSe reduced the activities of ALT and AST as well as the content of MDA, while concurrently elevated the activities of T-AOC, T-SOD and GSH to inhibit oxidative stress caused by Cd. In addition, the NSe group significantly increased mRNA expressions of Nrf2 pathway related molecules (Nrf2, HO-1, NQO-1, GST, GSH-Px, CAT and SOD) compared to the Cd group. In conclusion, NSe shows its potential to reduce Cd-induced liver injury by inhibiting oxidative stress and activating the Nrf2 pathway.